Intensive crop rotations and residue quality increase soil phosphorus lability under long-term no-till in tropical soils - Rigon, João Paulo Gonsiorkiewicz [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; Calonego, Juliano Carlos [UNESP]; Pavinato, Paulo Sérgio; Azevedo, Antonio Carlos; Rosolem, Ciro Antonio [UNESP] (Elsevier, 2022)
This study assessed soil Phosphorus (P) fractions and lability according to crops in rotation and crop residue P inputs under long-term no-till (NT) in weathered tropical soils. Two experiments were established in split-plot designs with fall-winter as the main plot and spring as the subplots. In one experiment, sunflower and triticale were grown in Typic Rhodudalf (TR) soil in fall-winter; in the other experiment, monocropped and intercropped ruzigrass and grain sorghum were grown in Rhodic Hapludox (RH) soil in fall-winter. In both experiments, sunn hemp, forage sorghum, and pearl millet were grown in the spring; an additional fallow treatment was established in spring in TR. Soybean was grown every year in the summer in both experiments. After 12 (TR) and 9 (RH) years, the crop residue quality (e.g. N content and lignin-N ratio) and P inputs of the various crops were assessed. In addition, soil P fractions were determined according to the Hedley procedure. High-quality residue enhanced P recycling by soybean under crop rotation with sunn hemp in both experiments, sunflower in TR, and ruzigrass in RH. Sunn hemp increased soil labile P by 13% compared with pearl millet in TR and by 40% compared with forage sorghum and pearl millet in RH. Forage sorghum in spring enhanced P mod-labile in TR, effect also observed for monocropped grain sorghum and ruzigrass in fall-winter in RH compared to both intercropped. In general, crop rotation under NT improved soil P lability, particularly the biological P pool, suggesting positive impacts from crop residue quality. The results of this study can be used to guide P fertilization strategies for NT cropping systems in tropical soils.
Keywords: Cover crop; P recycling; Soil management; Tropical soil